Нарушение согласования по роду в русской речи студентов-казахов: опыт корпусного исследования - Kazkenova, Aimgul; Kadyrova, Galina; Amanov, Amirkul (Przegląd Wschodnioeuropejski, 2023)
The studied examples of attributive phrases are cases of gender disagreement in written Russian of Kazakh students. The article shows that the gender disagreement is due to the absence of a gender category and the limited agreement in Kazakh, as well as the formal nature of the distribution of nouns by gender and the hardness of agreement in Russian. The material for the research was extracted from the Kazakh subcorpus of the Russian Learner Corpus. An attempt was made to conduct a quantitative analysis. The article describes the dependence of gender disagreement on the formal characteristics of the noun – the controller of the agreement, the case of the attributive phrase and partly the structure of the utterance.